Toni Morrison : writing the moral imagination - Smith, Valerie, 1956- (Chichester, West Sussex : Wiley, 2012)
'In this compelling new study, Valerie Smith analyzes the celebrated fiction of Morrison in relation to her critical writing about the process of reading and writing literature, the relationship between readers and writers, and the cultural contributions of African-American literature'--
Includes bibliographical references (p. [137]-146) and index.
Keywords: Morrison, Toni -- Criticism and interpretation